Malaria parasitaemia, anaemia and malnutrition in children less than 15 years residing in different altitudes along the slope of Mount Cameroon: prevalence, intensity and risk factors - Rene Ning Teh; Irene Ule Ngole Sumbele; Derick Ndelle Meduke; Samuel Takang Ojong; Helen Kuokuo Kimbi (Malaria Journal, 2018)
Abstract Background Malaria, anaemia and malnutrition are frequently co-existing diseases that cause significant morbidity and mortality particularly among children. This study measured the prevalence, intensity and evaluated risk factors for malaria parasitaemia, anaemia and malnutrition among children living at low versus high altitude settings in the Mount Cameroon area. Methods A cross-sectional community based survey involving 828 children aged 6 months to 14 years was conducted between July and November 2017. Malaria parasitaemia was confirmed by light microscopy, haemoglobin concentration was measured using an auto haematology analyser, nutritional status was determined from the anthropometric measurements collected, and socioeconomic status related variables by the use of questionnaire. Anaemia and malnutrition were defined according to World Health Organization standards. Associations between predictor variables and primary outcomes were assessed using logistic regression analysis. Results Malaria parasite and anaemia were prevalent in 41.7% and 56.2% of the children, respectively while, malnutrition prevalence was 34.8% with wasting, underweight and stunting occurring in 25.7%, 19.9% and 23.7% of them respectively. Overall malaria parasite geometric mean density was 413/µL of blood (range 100–27,060). The odds of having malaria parasitaemia was highest in children 5–9 years of age [odd ratio (OR) = 1.69, P = 0.006], living in lowland (OR = 1.48, P = 0.008) as well as those whose domestic water was collected from an open source (streams/springs) (OR = 1.81, P = 0.005) than their counterparts. Being < 5 years (OR = 3.15, P = < 0.001) or 5–9 years (OR = 2.20, P < 0.001) of age, having malaria parasite (OR = 2.07, P = < 0.001) and fever in the past 2 days (OR = 1.52, P < 0.04) were identified as significant risk factors of anaemia while the age group < 5 years was the only significant risk (OR = 3.09, P = < 0.001) associated with malnutrition. Conclusion While age specific attention ...